Association of bone-related biomarkers with femoral neck bone strength - Ning Xia; Yun Cai; Wei Wang; Chen Bao; Yunming Li; Qingyun Xie; Wei Xu; Da Liu (BMC Musculoskeletal Disorders, 2022)
Abstract Background Femoral neck fractures are the worst consequence of osteoporosis (OP), and its early prevention and treatment have become a public health problem. This study aims to investigate the relationship of bone-related biomarkers, femoral neck bone mineral density (BMD) and maximum load (Lmax), selecting the indicator which can reflect femoral neck bone loss and reduced bone strength. Methods A total of 108 patients were recruited from January 2017 to December 2019. Venous blood samples were collected from patients before total hip replacement, and femoral neck samples were collected during the surgery. Femoral neck BMD, femoral neck Lmax, bone-related markers (serum levels of bone turnover markers, protein expression of type I collagen (COL-I) and osteopontin (OPN) in femoral neck) were all measured and analyzed. Results The expression of COL-I in femoral neck were significantly decreased, whereas other markers were all significantly increased with the decreasing of femoral neck BMD and Lmax (P < 0.05). Among them, serum C-terminal telopeptide of type I collagen (CTX) levels and OPN expression of femoral neck were increased in osteopenia. In multiple linear regression analysis, CTX and OPN were both negatively correlated with femoral neck BMD and Lmax, and they were independent factors of femoral neck BMD and Lmax, whereas COL-I was independent factor affecting Lmax (P < 0.05). Besides, CTX was negatively correlated with COL-I (β = -0.275, P = 0.012) and positively correlated with OPN (β = 0.295, P = 0.003). Conclusions Compared with other indicators, serum CTX was more sensitive to differences in bone mass and bone strength of femoral neck, and could be considered as surrogate marker for OPN and COL-I.Early measurement of CTX could facilitate the diagnosis of osteopenia and provide a theoretical basis for delaying the occurrence of femoral neck OP and fragility fractures.